2001
DOI: 10.1667/0033-7587(2001)155[0269:mccotp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Calculation of the Primary Radical and Molecular Yields of Liquid Water Radiolysis in the Linear Energy Transfer Range 0.3–6.5 keV/μm: Application to137Cs Gamma Rays1

Abstract: Monte Carlo simulations of the radiolysis of neutral liquid water and 0.4 M H(2)SO(4) aqueous solutions at ambient temperature are used to calculate the variations of the primary radical and molecular yields (at 10(-6)s) as a function of linear energy transfer (LET) in the range approximately 0.3 to 6.5 keV/micrometer. The early energy deposition is approximated by considering short (approximately 20-100 micrometer) high-energy (approximately 300-6.6 MeV) proton track segments, over which the LET remains essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 70 publications
0
25
0
1
Order By: Relevance
“…The dose average LET value of 137 Cs gamma rays is reported as 0.91 (Meesungnoen et al 2001). Also reported values of dose average LET of 60 Co gamma rays range from 0.2-0.49 (Ibań ez et al 2009, International Commission on Radiation Units and Measurements (ICRU) report 16, 197016, , Ziegler et al 1985.…”
Section: Discussionmentioning
confidence: 99%
“…The dose average LET value of 137 Cs gamma rays is reported as 0.91 (Meesungnoen et al 2001). Also reported values of dose average LET of 60 Co gamma rays range from 0.2-0.49 (Ibań ez et al 2009, International Commission on Radiation Units and Measurements (ICRU) report 16, 197016, , Ziegler et al 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al (2009) reported that hydrogen peroxide (H 2 O 2 ), which is one of the reactive oxygen species (ROS) produced by lowand high-LET radiation exposure, decreases locomotory rate. On one hand, for 60 Co γ radiation at a neutral pH and room temperature, the G value of H 2 O 2 was 0.68, indicating that irradiation with 500 Gy produces 0.035 mM H 2 O 2 (Meesungnoen et al, 2001). On the other, its G value for high-LET radiation (100 keV/µm) was about 0.95 (Meesungnoen et al, 2005), resulted in 0.049 mM H 2 O 2 .…”
Section: Low Rbe For Locomotory Ratementioning
confidence: 99%
“…In aqueous biological samples, x-ray absorption is predominantly by water molecules. The primary free radical products of the radiolysis of water and their yields (molecules/100 eV) are ÁOH (2.80), e aq -(2.65), H 2 O 2 (0.68), and ÁH (0.60) (Meesungnoen et al 2001;Sehested et al 1973). There are many commercially available fluorescent ROS sensors that may respond to one or more of the above products.…”
Section: Introductionmentioning
confidence: 99%